Literature review: risk factors for neurogenic shock - Nadya Nur Aqilah; St Haeriyah Bohari; Sumarni, Sumarni; Moch Erwin Rachman; Nurhikmawati, Nurhikmawati (Jurnal EduHealth, 2024)
Spinal cord injury is most often associated as a contributing factor in causing neurogenic shock. Mostly associated with cervical and thoracic spine injuries. However, there are many factors that can cause neurogenic shock. This study explains the risk factors for trauma and non-trauma that can cause neurogenic shock. This type of study is a literature review using a narrative review design by collecting information through various sources related to risk factors for neurogenic shock. The results of article scoping found 15 study articles that could be used to provide answers to the problem formulation for this study. 6 study articles state that accidents are the biggest risk factor for neurogenic shock, spinal cord injuries tend to be influenced by accidents while driving which cause a loss of sensory and motor abilities. Apart from that, several other articles also state that violence, anesthesia, brain damage, tumors, infections, fractures and developmental abnormalities can be risk factors for neurogenic shock. Based on the findings of a review from various sources, it can be concluded that incidents of neurogenic shock are most often caused by risk factors for trauma due to traumatic injury to the spine.